AgNOR Expression in Canine Visceral Leishmaniosis - Bárbara Laurice Araújo Verçosa (Recent Research Advances in Biology Vol. 7, 2021)
One of the ways to assess cellular metabolism is through the AgNOR technique. Since NORs are related to protein synthesis, they are increased in number according to the increase in cell metabolism, which occurs when the cell enters the cell cycle. NORs are involved with active transcription during Leishmania spp infection and their activation can result in histopathological lesions depending on clinical status. Thus, AgNOR marker must be sought that can differentiate Leishmania-infected dogs with a higher risk of body impairment. The aim of this study was to revise the relations among histological lesions, AgNORs expression and clinical manifestations.